Bungo villagers’ rendition of nose and throat cancer - Ting, Su Hie; Podin, Yuwana; Monica Liaw, Kah Pei; Lipina, Jintang; Myra, Ungau (UNIMAS Publisher, 2023)
“We have a very good environment here. Our water is very clean”. This is the refrain I hear from the Bungo villagers when I visited them in November 2017, as part of the UNIMAS expedition team. Indeed, the rounded stones, shaped by the flowing water, are clearly visible in the river. The water is not yellowish like the Rejang River which I am used to seeing (I grow up in Sarikei and Sibu).